The vanishing sky - Binder, L. Annette, 1967- (Bloomsbury Publishing, 2020)
"In 1945, as the war in Germany nears its violent end, the Huber family is not yet free of its dangers or its insidious demands. Etta, a mother from a small, rural town, has two sons serving their home country: her elder, Max, on the Eastern front, and her younger, Georg, at a school for Hitler Youth. When Max returns from the front, Etta quickly realizes that something is not right-he is thin, almost ghostly, and behaving very strangely. Etta strives to protect him from the Nazi rule, even as her husband, Josef, becomes more nationalistic and impervious to Max's condition. Meanwhile, miles away, her younger son Georg has taken his fate into his own hands, deserting his young class of battle-bound soldiers to set off on a long and perilous journey home. The Vanishing Sky is a World War II novel as seen through a German lens, a story of the irreparable damage of war on the home front, and one family's participation - involuntary, unseen, or direct - in a dangerous regime."--Provided by publisher.